2021
DOI: 10.1002/cbin.11566
|View full text |Cite
|
Sign up to set email alerts
|

GPR39 promotes cardiac hypertrophy by regulating the AMPK–mTOR pathway and protein synthesis

Abstract: Hypertrophic growth of the cardiomyocytes is one of the core mechanisms underlying cardiac hypertrophy. However, the mechanism underlying cardiac hypertrophy remains not fully understood. Here we provided evidence that G protein‐coupled receptor 39 (GPR39) promotes cardiac hypertrophy via inhibiting AMP‐activated protein kinase (AMPK) signaling. GRP39 expression is overexpressed in hypertrophic hearts of humans and transverse aortic constriction (TAC)‐induced cardiac hypertrophy in mice. In neonatal cardiomyoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Recent studies have suggested that ribosome biogenesis plays an important role in cardiac hypertrophy by promoting or inhibiting the pathological process. 149 , 150 …”
Section: Ribosomes and Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that ribosome biogenesis plays an important role in cardiac hypertrophy by promoting or inhibiting the pathological process. 149 , 150 …”
Section: Ribosomes and Cardiovascular Diseases (Cvds)mentioning
confidence: 99%
“…Recent studies have suggested that ribosome biogenesis plays an important role in cardiac hypertrophy by promoting or inhibiting the pathological process. 149,150 The rDNA transcription rate is positively correlated with the degree of phosphorylation of RNA Pol I and the upstream binding factor (UBF). Studies have shown that the hypophosphorylated form of UBF blocks rDNA transcription by disrupting the UBF/SL1 complex.…”
Section: Ribosome and Cardiac Hypertrophymentioning
confidence: 99%
“…Furthermore, a screen of repurposed drugs found gandotinib as a potential contraceptive [ 74 ]. On the other hand, antagonism was recently suggested as beneficial in the treatment of myocardial infarction [ 14 ] or cardiac hypertrophy [ 15 ]. Enhanced expression of GPR39 has been documented in the aging human brain [ 17 ] and cancers [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Liao et al demonstrated that GPR39 inhibited AMPK signaling with mTOR and S6k1 activation, which induced the activation of de novo protein synthesis, leading to cardiac hypertrophy in mice. GPR39 overexpression in neonatal cardiomyocytes exacerbates angiotensin II-induced cardiac hypertrophy [ 65 ].…”
Section: Membrane Proteins Regulating Zinc Homeostasis In Calcium Hom...mentioning
confidence: 99%